Performance test of vertical dryer hybrid for drying Tuna fish. Issue 1 (January 2021) - Nurba, D; Mustaqimah, M; Fadhil, R; Darmansyah, D; Fajri, M
Abstract: Drying is the stage of processing tuna to extend the fish's shelf life until it is consumed. In general, fishers are drying the processed salted fish under direct sunlight. During the rainy season, conventional drying under the sun is impossible to inhibit the drying process; therefore, a mechanical dryer is needed. A greenhouse dehydrator (GHE) using a combination of solar and biomass energy is the right choice. The purpose of this study was to test the performance of the Vertical Dryer Hybrid to dry tuna. Drying is done by placing the tuna sample on four drying racks, then observing the moisture content, air humidity, solar irradiation, and the use of biomass energy. During 35 hours of observation, the GHE Vertical Dryer reduced the water content of tuna from 70.8% to 13.3% initial water content with average solar irradiation of 280.2 W / m 2 . The dryer's highest temperature during the drying process is 67°C, with an average of 46.7°C. The highest temperature in the environment is 37°C, with an average of 33.3°C. The highest RH in the dryer during the drying process is a 75% average of 43.8%, the highest RH in the environment is 79%, with 61.2%. The full use of bio-charcoal during drying is 5.5 kg, with the amount of energy obtained is 155.87 MJ, and the total solar energy obtained is 88.613 MJ with a total energy total of 244.49 MJ.